A arte do aconselhamento pastoral na reconstrução do ser humano: Projeto Girassol: abrindo novos caminhos - Romão, José Valdecy (2011)
The situations of social exclusion and the necessary linkages to the subjective formation process in these stories of young people and children of certain Brazilian contexts configures itself as suitable fields of action of clinical pastoral counseling bias, in other words, the strict application of the methodological steps proposed by professionals specific way liberating. This implies dialogue and reference to socialforming schemes that may relate to the subjectivity of children and youth, who live their experiences under the brand of social exclusion of those most fundamental aspects of human existence as food, housing and health, etc. From this perspective, this paper aims to establish possibilities of pastoral counseling, applied in the context of the Projeto Girassol, as a suitable means of helping these kids and these kids that they can exercise through speech and action, their concerns and bring to the light their idea about their own condition. This order aims to build certain perspective on life, namely, an authentic existence from the perspective of a certain theology of creation.